Constructions of space III: biblical spatiality and the sacred - Økland, Jorunn; Vos, Jacobus Cornelis de; Wenell, Karen J. ca. 21. Jh. (The Library of Hebrew Bible/Old Testament Studies, 2016)
"Constructions of Space III engages space both as focus in the texts under discussion, but also as analytical perspective. It explores more specifically how the Bible does not contain one, or even several, notions of sacred/holy space, even if there are undoubtedly many spaces described as such. It rather tries to trace how the discourses of space and those of the sacred intersect and interact in various writings of the Bible, more like points in a diagram, resulting in highly different ways of conceptualizing the sacred. A spatial-critical perspective can help us better understand how the relationship between notions of holiness and of space was a more dynamic one; as notions of space changed, so notions of holiness changed, and vice versa. Such a perspective also opens up further questions such as how the Temple's periphery is constructed, and how a human being can move and orient him- or herself in such a space over-loaded with meaning."--Bloomsbury Publishing